Compositions of foraminifera-rich turbidite sediments from the Shenhu area on the northern slope of the South China Sea: Implication for the presence of deep water bottom currents. (1st May 2017) - Li, Niu; Feng, Dong; Chen, Linying; Wang, Hongbin; Chen, Duofu
Graphical abstract: Highlights: High-resolution geochemical analysis of interbedded foraminifera-rich and dark-grey silt layers. Major element and grain size data indicate the foraminifera-rich layers are turbidites. Turbidite events might result from the sea level change since the last glaciations. U/Mo ratios could be indicator of interactive deposition between turbidite and bottom currents. Abstract: The sediments in gravity core DH-1, collected from Shenhu area on the northern slope of the South China Sea, are composed of two dark grey clay silt layers (A1 and A3 ) and two foraminifera-rich layers (A2 and A4 ) (A1 is the top layer and A4 is the bottom layer). Major and trace metal contents, along with grain size and mineralogic data suggest that these silt layers represent background hemipelagic sedimentation. Unlike silt layers, the intervening foraminifera-rich layerA4 exhibits a fining-upward trend, is distal turbidite. Grain size CM diagram and the sharp contacts between the foraminifera-rich layer A2 and the upper and lower layers suggest layer A2 is the result of depositional interaction between turbidite and bottom currents. AMS 14C dating of planktonic foraminifera indicate the age of the turbidite in A2 is between15.3 ka and 22.6 ka. We hypothesize that turbidite formation in this period was related to the increase supply of terrigenous matter since the Last Glacial Maximum. The rapid deposition of each turbidite led to reduced rates of oxygen diffusion into the sediment, allowing anoxic conditions develop in sediments and fostering U enrichment (>3.1 μg/g) in foraminifera-rich layer A4b . In contrast, decrease concentration of U and U/Mo ratios in foraminifera-rich layerA2, which is possibly due to U remobilization as a consequence of downward penetration of the oxidation front from the oxygen rich bottom currents. These new data suggest that authigenic U was quite sensitive to the inflow of bottom currents, and U/Mo ratios may indicate the depositional environmental change in relation to the bottom current action on the turbidite.